1996
DOI: 10.1074/jbc.271.32.19042
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Isoforms of Chicken Myomesin Are Generated by Alternative Splicing

Abstract: Myomesin is a high molecular weight protein that is present in the M-band of all fiber types of cross-striated skeletal muscle and heart. We have isolated two cDNAs encoding tissue-specific isoforms of chicken myomesin with calculated molecular masses of 174 kDa in skeletal muscle and 182 kDa in heart. Distinct sequences are found at the 3-end of the two cDNAs, giving rise to different C-terminal domains. Partial analysis of the gene structure has shown that in chicken, both isoforms are generated by alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
2
32
1
3
Order By: Relevance
“…Subsequently, two transcripts of different sizes were detected in chicken heart and skeletal muscle (8). The two isoforms differ only at their respective C termini, whereas the major part of the protein, which consists of a unique head domain followed by a conserved pattern of immunoglobulin-like and fibronectin type III domains, is identical.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequently, two transcripts of different sizes were detected in chicken heart and skeletal muscle (8). The two isoforms differ only at their respective C termini, whereas the major part of the protein, which consists of a unique head domain followed by a conserved pattern of immunoglobulin-like and fibronectin type III domains, is identical.…”
mentioning
confidence: 98%
“…It has recently been demonstrated that myomesin, an integral component of the M-band, is also expressed in several isoforms (8,12). Myomesin is present in all kinds of vertebrate striated muscle and is thought to play an important role in the integration of thick filaments with titin, a hypothesis based on its ability to bind both proteins in vitro (13).…”
mentioning
confidence: 99%
“…Myomesin can be alternatively spliced at the C-terminus, a variant being found in avian heart [27], and between domains My6 and My7, leading to the insertion of w100 amino acids (aa) (Figure 2). The resulting protein was initially described as skelemin [28], but later was proven to be a myomesin isoform [29] and was named EH-myomesin because it is the major isoform in the embryonic heart of all higher vertebrates [25].…”
Section: Trends In Cell Biologymentioning
confidence: 99%
“…Tem sido sugerido que a banda M apresenta um importante papel organizacional durante a miofibrilogênese, quando os filamentos grossos nascentes têm de montar e estar alinhados numa treliça regular hexagonal (Ehler et al, 1999;Wang et al, 1998;Yang et al, 2000). A miomesina e a proteína M, proteínas intimamente relacionadas, pertencem à família das proteínas imunoglobulinas, a qual os membros consistem de um domínio N-terminal único seguido de domínios de seqüência conservada semelhantes à imunoglobulina (Ig) e fibronectina tipo III (Bantle et al, 1996;Vinkemeier et al, 1993). Apesar dessa forte similaridade, essas duas proteínas exibem diferentes padrões de expressão.…”
Section: O Tecido Muscularunclassified
“…A miomesina e a proteína M, proteínas intimamente relacionadas, pertencem à família das proteínas imunoglobulinas, a qual os membros consistem de um domínio N-terminal único seguido de domínios de seqüência conservada semelhantes à imunoglobulina (Ig) e fibronectina tipo III (Bantle et al, 1996;Vinkemeier et al, 1993). Apesar dessa forte similaridade, essas duas proteínas exibem diferentes padrões de expressão.…”
Section: Cinco Proteínas Foram Identificadas Na Banda M De Vertebradosunclassified